Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results - Kiselev A. A., Kugai A. I., Avkhodiev G. I., Zimina N. V., Kot M. L., Viatkina I. N., Savinkina L. A., Ermakov D. N., Korshunov A. V., Kirsanova O. N., Karpov E. E., Zhaldak N. N., Mironova N. G., Korol N. V., Noskova M. V. (Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results, 2024)
this chapter reveals the toolkit for students’ training for the traditional endurance sports tournament «Bogatyrs of Yaroslav». The description of bogatyr is presented in the chapter based on the analysis of the literature. To conduct the experiment, special sets of exercises were developed for building the power abilities of the participants. A comparative analysis of the results of training the control and experimental groups indicates a significant advantage of the winners using the developed set of exercises.
Keywords: турнир; студенческие команды; характеристика богатыря; комплекс тренировочных упражнений; tournament; student teams; set of training exercises; characteristics of bogatyr